RESPONS PERTUMBUHAN DAN HASIL JAGUNG UNGU BERDASARKAN LETAK SUMBER BENIH PADA TONGKOL - Pamandungan, Yefta; Ogie, Tommy B. (Universitas Sam Ratulangi, 2017)
ABSTRACTÂ This research aims to 1) Study the growth and yield responses of purple corn location effect of the seed source on the ear to growth and yield of, 2) Determine the right location of the seed source on the ear to get the best of growth and yield of purple corn. Research conducted at the Kebun Percobaan (KP) Pandu, Faculty of Agriculture, University of Sam Ratulangi (Unsrat) Manado from April to July 2016. The plant material used is purple corn collected in the laboratory of Plant Science, Faculty of Agriculture, Unsrat. This research is using a randomized block design by four treatments, such as: L1 (base of the ear), L2 (center of the ear), L3 (tip of the ear), and L4 (all parts of the ear). Each treatment consisted of four replicates so that there are 16 experimental units. The results showed that treatment of the seed source location on the ear gives no significant effect on all components of growth. The treatment of L4 (base of the ear) produces the highest percentage of plants grown for 14 days after planting (42.75%), treatment of L2 (center of the ear) produces highest of the plant height at 20 and 40 days after planting (6.17 cm and 45.68 cm). On purple corn yield components, the treatment provides a significant effect on the weight of ear and length of the ear, but no significant effect on the diameter of the ear, number of seed rows per ear and weight of 100 seeds. Treatment L2 (center of the ear) produces the highest yields on the weight of the ear (36.90 g), length of the ear (10.49 cm), diameter of the ear (2.92 cm), the number of seed rows per ear (7.55 lines) and weight of 100 seeds (24.56 g). Keywords: corn, seed source location of corn, purple cornÂ